Value in Relations with the Final Customer - Łuczak, Miłosz (Studia Oeconomica Posnaniensia, 2017)
With the modern level of competition in the consumer goods market, customers have a wide choice of products and services, and by carrying subjective choices can maximize the satisfaction level of consumption. This creates a threat to companies who are forced to seek new ways of meeting the needs of its customers. Nowadays, various concepts focus on the benefits that result from establishing and strengthening relationships with final customers. The opportunity to participate in the design and development of the offer increases the satisfaction and loyalty of customers who are increasingly becoming co-creators of value.